Determinasi Penerimaan Wakaf Tunai: Penerapan Tata Kelola, Sosialisasi, dan Teknologi Berwakaf - Mutmainah; Utama Ahmed Dima; Sudirwo (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
This study was conducted to examine the factors that affect the receipt of cash waqf based on the perception of the Management of the Provincial Indonesian Waqf Agency (BWI) in Indonesia on the Implementation of Governance, Socialization and Waqf Technology. The research population is 34 Provincial Indonesian Waqf Bodies (BWI) in Indonesia. The unit of analysis in this study is 34 managers from the Indonesian Waqf Agency (BWI) Provincial in Indonesia, especially those who have functional positions. The data collection method is by questionnaire, while the data analysis technique used is multiple regression analysis and using the help of SPSS. The results of this study prove that the Perception of the Management of the Indonesian Waqf Agency (BWI) Provincial in Indonesia on the Implementation of Governance, Socialization and Technology of Waqf has an effect on Cash Waqf Receipts.